2019
DOI: 10.1111/apha.13335
|View full text |Cite
|
Sign up to set email alerts
|

Muscle atrophy and regeneration associated with behavioural loss and recovery of function after sciatic nerve crush

Abstract: Aim To resolve timing and coordination of denervation atrophy and the re‐innervation recovery process to discern correlations indicative of common programs governing these processes. Methods Female Sprague‐Dawley (SD) rats had a unilateral sciatic nerve crush. Based on longitudinal behavioural observations, the triceps surae muscle was analysed at different time points post‐lesion. Results Crush results in a loss of muscle function and mass (−30%) followed by a recovery to almost pre‐lesion status at 30 days p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 104 publications
(247 reference statements)
0
19
0
1
Order By: Relevance
“…Myod1 has been reported signi cantly up-regulated early after sciatic nerve compression, indicating that it started to play a role in initial muscle atrophy [32]. Studies have shown that mir-29b promotes atrophy of myotubes differentiated from C2C12 or primary myoblasts in vitro and contributes to skeletal muscle atrophy in response to different atrophic stimuli in vivo [27].…”
Section: Discussionmentioning
confidence: 99%
“…Myod1 has been reported signi cantly up-regulated early after sciatic nerve compression, indicating that it started to play a role in initial muscle atrophy [32]. Studies have shown that mir-29b promotes atrophy of myotubes differentiated from C2C12 or primary myoblasts in vitro and contributes to skeletal muscle atrophy in response to different atrophic stimuli in vivo [27].…”
Section: Discussionmentioning
confidence: 99%
“…It regulates muscle cell differentiation by inducing cell cycle arrest, which is a prerequisite for the initiation of myogenesis. Myod1 has been reported signi cantly up-regulated early after sciatic nerve compression, indicating that it started to play a role in initial muscle atrophy [23].RELA proto-oncogene (Rela), a component of the NFkappa B complex, and nuclear factor kappa B subunit 1 (Nfkb1) jointly constitute a transcriptionally active NF-kappa B dimer, which participates in the expression of genes in the processes of immunity, in ammation, and apoptosis [24]. Nuclear factor Kappa B (NF-κB) has also been reported to be a prominent signaling molecule in the pathogenesis of skeletal muscle atrophy, and many muscular atrophy-related genes, including MuRF1, MyoD and cyclin D ubiquitin-binding enzyme (E2), are its target gene [25].…”
Section: Discussionmentioning
confidence: 99%
“…Myod1 has been reported signi cantly up-regulated early after sciatic nerve compression, indicating that it started to play a role in initial muscle atrophy [23].RELA proto-oncogene (Rela), a component of the NFkappa B complex, and nuclear factor kappa B subunit 1 (Nfkb1) jointly constitute a transcriptionally active NF-kappa B dimer, which participates in the expression of genes in the processes of immunity, in ammation, and apoptosis [24]. Nuclear factor Kappa B (NF-κB) has also been reported to be a prominent signaling molecule in the pathogenesis of skeletal muscle atrophy, and many muscular atrophy-related genes, including MuRF1, MyoD and cyclin D ubiquitin-binding enzyme (E2), are its target gene [25].…”
Section: Discussionmentioning
confidence: 99%